Transforming Orthopaedic care with Interprofessional Education: Challenges, Strategies, and Outcomes - Janki Sharan Bhadani; Raju Vaishya; John Mukhopadhaya (National Board of Examinations Journal of Medical Sciences)
Introduction: Interprofessional education (IPE) is critical to improve teamwork and collaboration in orthopaedics, so ultimately improving patient care. This study is about the integration of IPE into orthopaedic practice, the challenges of implementation of IPE and, its impact on outcomes. Methods: A comprehensive review of the literature from 2005 to 2024 was conducted using PubMed, Google Scholar, and Scopus. Studies focusing on the role of IPE in patient care and teamwork were included. Non-peer-reviewed articles were excluded. Results: IPE improves clinical outcomes by improving communication, role clarity, and shared decision-making in orthopaedic teams. Effective strategies such as case-based learning and simulation training strengthen collaborative skills. Despite challenges such as time constraints and institutional resistance, customised training and curriculum integration provide viable solutions. Conclusions: Incorporating IPE into orthopaedic education is critical to promote teamwork and improve patient outcomes. Addressing challenges and fostering collaboration can drive innovation in orthopaedic care and enhance healthcare delivery around the world.